Feet swelling in a multistage ultraendurance triathlete: a case study - Knechtle, Beat (Int J Gen Med, 2015)
Recent studies investigating ultraendurance athletes showed an association between excessive fluid intake and swelling of the lower limbs such as the feet. To date, this association has been investigated in single-stage ultraendurance races, but not in multistage ultraendurance races. In this case study, we investigated a potential association between fluid intake and feet swelling in a multistage ultraendurance race such as a Deca Iron ultratriathlon with ten Ironman triathlons within 10 consecutive days. A 49-year-old well-experienced ultratriathlete competed in autumn 2013 in the Deca Iron ultratriathlon held in Lonata del Garda, Italy, and finished the race as winner within 129:33 hours:minutes. Changes in body mass (including body fat and lean body mass), foot volume, total body water, and laboratory measurements were assessed. Food and fluid intake during rest and competing were recorded, and energy and fluid turnovers were estimated. During the ten stages, the volume of the feet increased, percentage body fat decreased, creatinine and urea levels increased, hematocrit and hemoglobin values decreased, and plasma [Na(+)] remained unchanged. The increase in foot volume was significantly and positively related to fluid intake during the stages. The poststage volume of the foot was related to poststage total body water, poststage creatinine, and poststage urea. This case report shows that the volume of the foot increased during the ten stages, and the increase in volume was significantly and positively related to fluid intake during the stages. Furthermore, the poststage volume of the foot was related to poststage total body water, poststage creatinine, and poststage urea. The continuous feet swelling during the race was most probably due to a combination of a high fluid intake and a progressive decline in renal function (ie, continuous increase in creatinine and urea), leading to body fluid retention (ie, increase in total body water).